(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
This paper aims to reveal how paying manufacturing workers with living wages instead of minimum wages increases business costs and alters comparative advantages among 98 multi-tier supply chains, as well as to find the level of wage increase to make the lowest cost supply chain lose its competitiveness. Both scenario and sensitivity analyses are employed. The findings show that paying living wages neither significantly increases business costs nor influences comparative advantages of the 98 supply chains, implying no manufacturing relocation and unemployment. Furthermore, the findings present the importance of proximity between materials and product manufacturing locations. Lastly, governments can potentially create their location competitiveness supporting low transportation costs and port fees, and incentivizing materials manufacturing to attract other manufacturing activities.